PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL DAN MINAT BELAJAR MATEMATIKA KELAS V SD - Azzahra, Kailifa Zakia; Muhroji, Muhroji (STKIP Persada Khatulistiwa Sintang, 2025)
The aim of this study is to improve mathematics learning outcomes and interest through the implementation of the Culturally Responsive Teaching (CRT) approach among fifth-grade elementary school students. This research is a Classroom Action Research (CAR), with the research subjects being 28 fifth-grade students of SD Negeri Soropadan in the 2023/2024 academic year. Data collection methods included observation and tests. Observation was used to collect data on students' interest in learning mathematics, while test results provided data on learning outcomes. The collected data were analyzed using a descriptive-qualitative approach. The results showed that (1) there was an increase in the average score percentage of students' interest in learning mathematics by 13.9%, from 57.4% in the first cycle to 71.3% in the second cycle; and (2) there was an improvement in the average score of mathematics learning outcomes by 30%, from 66.33 in the first cycle to 81.67 in the second cycle. Based on the findings, the application of the Culturally Responsive Teaching approach in mathematics subjects in Grade V of SD Negeri Soropadan can enhance both students' interest and learning outcomes in mathematics.